A web-based registry for patients with sarcoidosis - Gerke, Alicia K; Tang, Fan; Cozier, Yvette C; Lash, Michael T; Schappet, James; Phillips, Emily; Polgreen, Philip M (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background/Objective: The objective is to present the development of a novel web-based patient registry for sarcoidosis. We describe recruitment efforts and assess efficacy of internet-based advertising on recruitment. Methods: “Worldwide Sarcoidosis Research Study (WISE)” started in 2011 under the domain www.sarcoidstudy.org. The registry includes thirteen patient-reported surveys about patient characteristics, diagnosis, and treatment. Effects of two internet-based advertising methods (geographically-broad versus geographically-targeted to high sarcoidosis search areas) on recruitment were analyzed with time series regression. Results: Since 2011, over 1500 participants have registered (82% whites, 9% African Americans, 5% mixed, 4% other), with 23% of participants providing saliva samples for DNA. Median age is 43 years (range 21-80). African Americans were more frequently recruited via support groups, while whites had a higher frequency of finding the registry via internet. Generalized internet-based advertising significantly improved recruitment in all demographic groups (p